2016
DOI: 10.3390/su8080682
|View full text |Cite
|
Sign up to set email alerts
|

Drivers for the Adoption of Eco-Innovations in the German Fertilizer Supply Chain

Abstract: Abstract:Use of fertilizers has enabled a massive increase in crop production yields. However, this has come with severe negative externalities (e.g., greenhouse gas emission; eutrophication of non-agricultural ecosystems). Eco-innovations are one option to reduce the environmental impact of fertilizers without compromising fertilizer productivity. Although numerous eco-innovations in the domain of fertilizers are available, they have not yet seen a sufficient adoption rate. In this paper we explore main drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 68 publications
(96 reference statements)
0
19
0
3
Order By: Relevance
“…A research conducted by Hasler et al (2016) shows that the farmers are the most skeptical towards fertilizer eco-innovation of the whole supply chain [27]. Hasler et al (2016) concluded that both farmers and suppliers consider legal regulations as a driving force for environmental requirements and eco-innovation [27]. Further research on the opinion of farmers could shed more light on the opinions of farmers towards the use of struvite or other recovered P products.…”
Section: Social Aspects: Interview Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A research conducted by Hasler et al (2016) shows that the farmers are the most skeptical towards fertilizer eco-innovation of the whole supply chain [27]. Hasler et al (2016) concluded that both farmers and suppliers consider legal regulations as a driving force for environmental requirements and eco-innovation [27]. Further research on the opinion of farmers could shed more light on the opinions of farmers towards the use of struvite or other recovered P products.…”
Section: Social Aspects: Interview Resultsmentioning
confidence: 99%
“…Growing awareness about the phosphate problem could play a helping hand in the use of recycled phosphates. A research conducted by Hasler et al (2016) shows that the farmers are the most skeptical towards fertilizer eco-innovation of the whole supply chain [27]. Hasler et al (2016) concluded that both farmers and suppliers consider legal regulations as a driving force for environmental requirements and eco-innovation [27].…”
Section: Social Aspects: Interview Resultsmentioning
confidence: 99%
“…More importantly, sustainable innovation paradox management requires inter-organizational cooperation, because innovation relies on a sustainable ecosystem consisting of interactions among organizations, policies, and the environment [12]. This implies that the focal firm plays an important role in managing sustainable innovation paradox effectively [7,13]. Published works found that ambidextrous capability is an effective way of resolving the paradox [14], but few works discussed the sustainable innovation paradox of the focal firm based on it.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of them are still not used at farm level although they might have a high potential in decreasing CO 2 emissions (Renni and Heffer 2010). Based on an intensive survey, Hasler et al (2016) have already shown that most of these agricultural eco-innovations are not relevant for in-depth studies in GHG emissions, because of their insignificant market penetration. However, three specific fertilizer eco-innovations with high importance for the fertilizer sector and potential of GHG emission reduction could be identified: stabilized nitrogen fertilizers (SNF), fertigation (FG) and secondary raw material fertilizers (SRMF).…”
mentioning
confidence: 99%
“…Ecoinnovations are innovations that aim at improving the production, application or exploring of a product that is novel and which results, throughout its life cycle, in a reduction of environmental risk, pollution and negative impacts of resource use (including energy use) compared to relevant alternatives (Kemp et al 1998, Rennings 2000, Ekins 2010). Eco-innovations are innovations that reduce the environmental impact and potentially lead to a more responsible application of fertilizers in order to achieve low input/high output farming systems (Hasler et al 2016).…”
mentioning
confidence: 99%